Numerical and theoretical analyses of settlements of strip shallow foundations on normally consolidated clays under partially drained conditions. Issue 12 (7th December 2021) - Flessati, Luca; di Prisco, Claudio; Callea, Fabio
Abstract : In the geotechnical community, the macroelement approach nowadays is largely considered to be a successful theoretical tool for solving soil–structure interaction problems. This approach is based on the definition of a generalised constitutive law putting in relation a small number of suitably defined generalised stress/strain variables. The macroelement formulations proposed in the literature take into consideration either drained or undrained cases, but disregard the hydro-mechanical coupling. In this paper, the authors intend to generalise the theory by introducing a new formulation for shallow foundations overpassing this limitation and capable of accounting for the influence of loading rate on the system response. To conceive and to calibrate the model, the authors numerically analysed the case of a shallow foundation positioned on a normally consolidated clayey soil stratum whose mechanical behaviour is reproduced by means of the modified Cam Clay model. Finally, the approach is discussed critically from the perspective of its use as a design tool according to approaches based on the ultimate limit state and displacement.